Analysis of cardiomyocyte clonal expansion during mouse heart development and injury - Konstantina-Ioanna Sereti; Ngoc B. Nguyen; Paniz Kamran; Peng Zhao; Sara Ranjbarvaziri; Shuin Park; Shan Sabri; James L. Engel; Kevin Sung; Rajan P. Kulkarni; Yichen Ding; Tzung K. Hsiai; et al. (Nature Communications, 2018)
During cardiac tissue formation it is unclear whether newly generated myocytes originate from cardiac progenitor cells or from pre-existing cardiomyocytes. Here, the authors use a stochastic four-colour reporter system (Rainbow) to identify the source of new cardiomyocytes during mouse development.